A New Approach to Measure Gas Holdup in Industrial Flotation Machines Part I: Demonstration of Working Principle - Maldonado-Saavedra, M (Elsevier Ltd, 2018)
A new approach for continuous measurement of gas holdup, based on the generation and measurement of a bubble-free pulp flow using a gas-exclusion cell immersed in the collection zone of industrial flotation machines is introduced and demonstrated. The gas-exclusion cell, a device that works exclusively on hydrodynamics effects caused by its design, prevents the entrance of bubbles and fills continuously only with mineral pulp; the higher density of the fluid inside the cell originates a circulating pulp flow through the unit that is proportional to the gas holdup. Continuous tracking of the pulp flow velocity, using a magnetic flowmeter connected to the gas-exclusion cell, allows online calculation of the gas holdup using an equation derived from a mechanical energy balance. Design constraints and results of the hydrodynamic characterization of demonstration units are discussed. The results of two-phase prototype testing demonstrated that the approach is robust and provides reliable gas holdup measurements and tracking. © 2018 Elsevier Ltd